Conducting Polymer‐Based Biocomposites Using Deoxyribonucleic Acid (DNA) as Counterion. Issue 3 (18th November 2019) - Tekoglu, Serpil; Wielend, Dominik; Scharber, Markus Clark; Sariciftci, Niyazi Serdar; Yumusak, Cigdem
Abstract: In this work, the preparation of conducting polymer‐based composites using a biological anionic polymer based on salmon deoxyribonucleic acid (DNA) is presented. The most commonly used polymers poly(3, 4‐ethylenedioxythiophene) (PEDOT), as well as polypyrrole, are polymerized in the presence of DNA. Since conjugated polymers are in the polycationic state in their electrically conducting form, the role of the counterion is now fulfilled by the low cost biomolecule DNA as an alternative material, which is also a polyanion thanks to its phosphate chain. The resulting synthesized material is a conducting polymer–DNA biocomposite. Such materials are highly attractive for the rising field of bioelectronics and biosensors, especially in organic electrochemical transistors (OECTs) and ion pumps. OECTs made of these conducting polymer biocomposites are fabricated and their electrochemical device operation is compared to the most widely used PEDOT:polystyrenesulfonate. Abstract : The synthesis and film formation of DNA‐based conductive biocomposites, poly(3, 4‐ethylenedioxythiophene):DNA and polypyrrole:DNA are described. Spectroscopic properties, conductivity, and morphology results are explored. The transparent conductive biocomposites are investigated in organic electrochemical transistor device composition for their potential use in bioactive and biocompatible systems.